Cognitive functions in multiple sclerosis: impact of gray matter integrity. (April 2014) - Llufriu, Sara; Martinez-Heras, Eloy; Fortea, Juan; Blanco, Yolanda; Berenguer, Joan; Gabilondo, Iñigo; Ibarretxe-Bilbao, Naroa; Falcon, Carles; Sepulveda, Maria; Sola-Valls, Nuria; Bargallo, Nuria; Graus, Francesc; et al.
Objectives: Our aim was to investigate the impact of gray matter (GM) integrity on cognitive performance in multiple sclerosis (MS), and its relationship with white matter (WM) integrity and presence of lesions. Methods: Sixty-seven patients with MS and 26 healthy controls underwent voxel-based analysis of diffusion tensor images (DTI) in GM and tract-based spatial statistics (TBSS) from WM to identify the regional correlations between cognitive functions and integrity. Lesion probability mapping (LPM) was generated for correlation analysis with cognition. Multiple linear regression analyses were used to identify the imaging measures associated with cognitive scores. Results: Compared with controls, patients showed abnormal DTI indices in several GM regions and in most WM tracts. Impairment in DTI indices in specific GM regions was associated with worse performance of distinct cognitive functions. Those regions showed anatomical correspondence with cognitively relevant tracts in TBSS and LPM. The combination of regional GM and WM DTI and lesion volume accounted for 36–51% of the variance of memory and attention scores. Regional GM DTI explained less than 5% of that variance. Conclusion: GM and WM integrity of specific networks influences cognitive performance in MS. However, GM damage assessed by DTI only adds a small increment to the explained variance by WM in predicting cognitive functioning.